2007
DOI: 10.1002/dvdy.21089
|View full text |Cite
|
Sign up to set email alerts
|

Isoform‐specific interaction of Flamingo/Starry Night with excess Bazooka affects planar cell polarity in the Drosophila wing

Abstract: Epithelia display two types of polarity, apical-basal and planar cell polarity (PCP), and both are crucial for morphogenesis and organogenesis. PCP signaling pathways comprise transmembrane proteins, such as Flamingo/Starry Night, and cytoplasmic, membrane-associated proteins such as Dishevelled. During establishment of PCP in the Drosophila wing, PCP proteins accumulate apically in distinct "cortical domains" on proximal and distal plasma membranes. This finding suggests that their localized function depends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…No interaction was observed between in vitro translated Rbsn-5 and the cytoplasmic tail of both Fmi isoforms (Fmi and Stan) so far described (Wasserscheid et al, 2007) in GST pull-down assays (data not shown). It remains possible that the recruitment of Rbsn-5 by Fmi might require an intermediate binding partner.…”
Section: Flamingo But Neither Strabismus Nor Frizzled Is Rate Limitmentioning
confidence: 82%
See 1 more Smart Citation
“…No interaction was observed between in vitro translated Rbsn-5 and the cytoplasmic tail of both Fmi isoforms (Fmi and Stan) so far described (Wasserscheid et al, 2007) in GST pull-down assays (data not shown). It remains possible that the recruitment of Rbsn-5 by Fmi might require an intermediate binding partner.…”
Section: Flamingo But Neither Strabismus Nor Frizzled Is Rate Limitmentioning
confidence: 82%
“…Bound proteins were eluted from the beads, separated by SDS-PAGE and analysed by autoradiography. GST-Fmi and GST-Stan were used as previously described (Wasserscheid et al, 2007).…”
Section: In Vitro Binding Assaymentioning
confidence: 99%
“…Binding sites have been mapped between Stbm and Pk, as well as between Dsh and Dgo (Jenny et al., 2003, Jenny et al., 2005), and Stbm, Pk, and Dsh contain dimerization motifs (Jenny et al., 2003, Kishida et al., 1999). In addition to this, Fmi, Fz, Stbm, and Dsh contain putative PDZ (PSD-95, Discs Large, ZO-1) binding motifs of unknown function, which may interact with PDZ-containing scaffolding factors (Wolff and Rubin, 1998, Djiane et al., 2005, Wasserscheid et al., 2007, Johnston et al., 2013). Membrane interaction motifs, for example the DEP (Dishevelled, Egl10, and Pleckstrin) domain (Simons et al., 2009) and the Pk prenylation motif (Jenny et al., 2003, Lin and Gubb, 2009, Strutt et al., 2013b), may also promote association of the core proteins to junctions independently of protein-protein interaction sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interacting Arm isoform ends with –DTDC which does not match any peptides identified, and thus suggests a binding mechanism outside of the peptide binding pockets. Finally, the isoform of Flamingo that was pulled down from cell lysates with the tandem Baz PDZ1-3 protein has a C-terminus of -DDETTV [21], matching all Baz PDZ2 peptides at the P 0 position, and two additionally at the P -3 position and one additionally at the P -5 position. As more proteins are found to interact with Baz, the peptides we have identified will hopefully aid in mapping their specific interaction sites.…”
Section: Discussionmentioning
confidence: 99%
“…Using in vitro binding assays, purified C-terminal portions of the adherens junction components Echinoid and Armadillo ( Drosophila β-catenin) have been shown to bind a purified fusion protein containing all three PDZ domains of Baz in tandem [20]. Also, a purified fusion protein of the three PDZ domains of Baz has been shown to pull down a specific isoform of the atypical cadherin Flamingo from wing imaginal disk extracts [21].…”
Section: Introductionmentioning
confidence: 99%